Characteristics of Infection Immunity Regulated by Toxoplasma gondii to Maintain Chronic Infection in the Brain - Hwang, Young Sang; Shin, Ji-Hun; Yang, Jung-Pyo; Jung, Bong-Kwang; Lee, Sang Hyung; Shin, Eun-Hee (Frontiers in Immunology, 2018)
To examine the immune environment of chronic Toxoplasma gondii infection in the brain, the characteristics of infection-immunity (premunition) in infection with T. gondii strain ME49 were investigated for 12 weeks postinfection (PI). The results showed that neuronal cell death, microglia infiltration and activation, inflammatory and anti-inflammatory cytokine expression, Stat1 phosphorylation, and microglia activation and inflammatory gene transcripts related to M1 polarization in the brain were increased during the acute infection (AI) stage (within 6 weeks PI), suggesting that innate and cellular inflammatory response activation and neurodegeneration contributed to excessive inflammatory responses. However, these immune responses decreased during the chronic infection (CI) stage (over 6 weeks PI) with reductions in phosphorylated STAT1 (pSTAT1) and eosinophilic neurons. Notably, increases were observed in transcripts of T-cell exhaustion markers (TIM3, LAG3, KLRG1, etc.), suppressor of cytokines signaling 1 protein (SOCS1), inhibitory checkpoint molecules (PD-1 and PD-L1), and Arg1 from the AI stage (3 weeks PI), implying active immune intervention under the immune environment of M1 polarization of microglia and increases in inflammatory cytokine levels. However, when BV-2 microglia were stimulated with T. gondii lysate antigens (strain RH or ME49) in vitro, nitrite production increased and urea production decreased. Furthermore, when BV-2 cells were infected by T. gondii tachyzoites (strain RH or ME49) in vitro, nitric oxide synthase and COX-2 levels decreased, whereas Arg1 levels significantly increased. Moreover, Arg1 expression was higher in ME49 infection than in RH infection, whereas nitrite production was lower in ME49 infection than in RH infection. Accordingly, these results strongly suggest that immune triggering of T. gondii antigens induces M1 polarization and activation of microglia as well as increase NO production, whereas T. gondii infection induces the inhibition of harmful inflammatory responses, even with M1 polarization and activation of microglia and Th1 inflammatory responses, suggesting a host–parasite relationship through immune regulation during CI. This is a characteristic of infection immunity in infection with T. gondii in the central nervous system, and SOCS1, a negative regulator of toxoplasmic encephalitis, may play a role in the increase in Arg1 levels to suppress NO production.